Prognostic value of simple risk index and plasma volume status in patients with acute decompensated heart failure. (14th October 2021) - Yamada, T; Watanabe, T; Morita, T; Kawasaki, M; Kikuchi, A; Kawai, T; Seo, M; Nakmura, J; Kayama, K; Fukunami, M
Abstract: Background: Increased heart rate (HR) and low systolic blood pressure (SBP) are associated with adverse clinical outcomes in patients admitted for acute decompensated heart failure (ADHF), and simple risk index (SRI) based on easily assessed clinical characteristics (age, HR, and SBP) provides prognostic information. On the other hand, plasma volume (PV) expansion plays an essential role in heart failure, and PV status is has been reported to be associated with adverse outcomes in ADHF patients. However, there is no information available on the value of the combination of SRI and PV status in patients admitted for ADHF. Methods and results: We studied 301 patients admitted for ADHF. At the admission, SRI was calculated as (HR x [age/10] 2 )/SBP. PV status was calculated as the following: Actual PV = (1 − hematocrit) x [a + (b x body weight)] (a=1530 in males and a=864 in females, b=41 in males and b=47.9 in females), Ideal PV = c x body weight (c=39 in males and c=40 in females), and PV status = [(actual PV − ideal PV)/ideal PV] x 100(%). During a follow-up period of 4.3±3.2 yrs, 95 patients had all-cause death (ACD) and 68 patients had cardiovascular death (CVD). At multivariate Cox analysis, SRI and PV status were significantly associated with ACD and CVD, independently of the prior history of heart failure hospitalization and serum creatinine and sodium levels, after the adjustment with serum albumin level and anemia. Patients with both greater SRI (≥35.1 by ROC analysis; AUC 0.599 [0.524–0.674]) and greater PV status (≥8.1% by ROC analysis; AUC 0.625 [0.550–0.700]) had a significantly higher risk of ACD and CVD than those with either or none of them (ACD: 49% vs 27% vs 24%, p<0.0001, CVD: 39% vs 18% vs 15%, p<0.0001, respectively). Conclusion: The combination of SRI and PV status might be useful for stratifying patients at risk for the total mortality and cardiovascular death in patients with ADHF. Funding Acknowledgement: Type of funding sources: None.